Secondhand Smoke Exposure in Toddlerhood and Cognitive Abil¬ity among Malaysian Adolescents - Najihah Zainol ABIDIN; Aziemah ZULKIFLI; Emilia Zainal ABIDIN; Anita Abd RAHMAN; Zailina HASHIM; Irniza RASDI; Sharifah Norkhadijah Syed ISMAIL (Tehran University of Medical Sciences, 2015)
Background: Secondhand Smoke (SHS) exposure has been reported to cause a number of adverse health effects. Although studies have been conducted to identify the link between SHS exposure and cognitive functioning of children, its relationship is still unclear. This study aimed to identify the association of prenatal and postnatal SHS exposure with cognitive ability among adolescents. Methods: A total of 370 adolescents aged 13-14 years old in two states in Malaysia participated in this study. A modified Global Youth Tobacco Survey questionnaire was used to assess exposure to SHS. Parental-administered questionnaire was used to obtain information on parental smoking and prenatal SHS exposure. Cognitive ability was objectively measured using Wechsler Nonverbal Scale of Ability. Results: 75.4% and 24.6% adolescents were identified to have cognitive ability categorized as high (>90marks) and low (≤90marks), respectively. From the logistic analysis adjusting for confounders, adolescents with SHS exposure in toddlerhood (≤2years old) were three times more likely to have lower cognitive ability compared to those without exposure (Adjusted Odds Ratio (AOR), 2.89; 95% Confidence Interval (CI), 1.21-6.83). School absenteeism was associated with lower cognitive ability. Conclusion: Exposure to SHS during toddlerhood was linked to lower cognitive ability among adolescents. The findings of this study emphasize the need for preventing involuntary toddlerhood SHS exposure from parents and indirectly encourage home smoking restriction practices among Malaysian citizens.   Keywords:  Passive smoking, Adolescents, Cognitive ability, Youth, Tobacco smoke